Muslim Women Issues in the Family: Toward an Enlightened Fiqh Construction - Sikandar Shah, Mek Wok Mahmud Sayed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Muslim Women Issues in the Family: Toward an Enlightened Fiqh Construction